The Light Chain IgLV3-21 Defines a New Poor Prognostic Subgroup in Chronic Lymphocytic Leukemia: Results of a Multicenter Study - Stamatopoulos, Basile; Smith, Thomas; Crompot, Emerence; Pieters, Karlien; Clifford, Ruth; Mraz, Marek; Robbe, Pauline; Burns, Adam; Timbs, Adele; Bruce, David; Hillmen, Peter; Meuleman, Nathalie; et al. (Clinical cancer research, 2018)
Purpose: Unmutated (UM) immunoglobulin heavy chain variable region (IgHV) status or IgHV3-21 gene usage is associated with poor prognosis in chronic lymphocytic leukemia (CLL) patients. Interestingly, IgHV3-21 is often co-expressed with light chain IgLV3-21, which is potentially able to trigger cell-autonomous BCR-mediated signaling. However, this light chain has never been characterized independently of the heavy chain IgHV3-21.Experimental Design: We performed total RNA sequencing in 32 patients and investigated IgLV3-21 prognostic impact in terms of treatment-free survival (TFS) and overall survival (OS) in 3 other independent cohorts for a total of 813 patients. IgLV3-21 presence was tested by real-time PCR and confirmed by Sanger sequencing.Results: Using total RNA sequencing to characterize 32 patients with high-risk CLL, we found a high frequency (28%) of IgLV3-21 rearrangements. Gene set enrichment analysis revealed that these patients express higher levels of genes responsible for ribosome biogenesis and translation initiation (P < 0.0001) as well as MYC target genes (P = 0.0003). Patients with IgLV3-21 rearrangements displayed a significantly shorter TFS and OS (P < 0.05), particularly those with IgHV mutation. In each of the three independent validation cohorts, we showed that IgLV3-21 rearrangements-similar to UM IgHV status-conferred poor prognosis compared with mutated IgHV (P < 0.0001). Importantly, we confirmed by multivariate analysis that this was independent of IgHV mutational status or subset #2 stereotyped receptor (P < 0.0001).Conclusions: We have demonstrated for the first time that a light chain can affect CLL prognosis and that IgLV3-21 light chain usage defines a new subgroup of CLL patients with poor prognosis. Clin Cancer Res; 24(20); 5048-57. ©2018 AACR.
Keywords: Gene Ontology; lehké řetězce imunoglobulinů; Humans; genová ontologie; Sequence Analysis, DNA; Immunoglobulin Variable Region; Biomarkers, Tumor; Female; mutace; Immunoglobulin Light Chains; lidé; chronická lymfatická leukemie; výpočetní biologie; peptidy; Peptides; nádorové biomarkery; sekvenční analýza DNA; Leukemia, Lymphocytic, Chronic, B-Cell; Computational Biology; chromozomální aberace; ženské pohlaví; Chromosome Aberrations; Male; prognóza; regulace genové exprese u leukemie; stanovení celkové genové exprese; transkriptom; klinické zkoušky jako téma; Transcriptome; Clinical Trials as Topic; Gene Expression Profiling; Mutation; mužské pohlaví; Prognosis; variabilní oblast imunoglobulinu; Gene Expression Regulation, Leukemic